Comprehensive review of α-carboline alkaloids: Natural products, updated synthesis, and biological activities - Li, Deping; Yang, Renze; Wu, Jun; Zhong, Bin; Li, Yan (Frontiers in Chemistry, 2022)
Several medicinal plants containing α-carboline based molecules have long been used in clinical application, and implitapide (a molecule containing α-carboline moiety) has reached clinical trails to alleviate atherosclerosis, suggesting α-carboline is a promising scaffold for medicinal chemistry. In recent decades, accumulating evidence shows that α-carboline derivatives possess diverse bioactivities including anti-tumor, anti-microbial, anti-atherosclerosis, anti-Alzheimer's disease, anti-inflammatory, and neuroprotective activities. However, hitherto, there is no comprehensive review to systematically summarize this important class of alkaloids. In this perspective, this paper represents the first review to provide a comprehensive description of α-carbolines including natural products, updated literature of synthesis, and their diverse biological activities. In the biological activity section, the targets and the main structure activity relationships (SARs) will be presented. Finally, future directions of this class of compounds will be discussed. This review will be helpful in understanding and encouraging further exploration for this group of alkaloids.